Increasing Competitive Advantage with Creativity and Innovation: The Moderating Effect of Digital Leadership - Umayna, Farah; Shalahuddin, Shalahuddin; Darmawan, Dedy; Long, Ang Hong; Gulabdin, Shaierah; Sondoh, Stephen Laison; Sidin, Julian Paul (Advances in Human Resource Management Research, 2025)
Purpose: This study explores how psychological empowerment influences competitive advantage through creativity and innovative work behavior while also analyzing the moderating role of digital leadership. The study emphasizes the importance of building sustainable competitive strategies in Micro, Small, and Medium Enterprises (MSMEs) through innovation-driven human capital. Research Design and Methodology: A quantitative approach was employed, using a structured questionnaire distributed to 254 MSMEs in South Sulawesi, Indonesia. Data analysis was conducted through Structural Equation Modeling using the Partial Least Squares (SEM-PLS) method to test direct and indirect effects among the studied variables. Findings and Discussion: The results reveal that psychological empowerment significantly affects creativity and innovative work behavior, not a competitive advantage. Creativity influences innovative work behavior but does not directly lead to competitive advantage. Innovative work behavior significantly contributes to competitive advantage. Moreover, creativity mediates the relationship between psychological empowerment and innovative behavior, but not with a competitive advantage. Innovative work behavior mediates both psychological empowerment and creativity in achieving competitive advantage. Digital leadership strengthens the transformation of creativity into innovative behavior. It reinforces the impact of innovative behavior on competitive advantage but does not enhance the direct effects of psychological empowerment and creativity on competitiveness. Implications: This study offers theoretical and managerial insights by highlighting the strategic role of innovation and digital leadership in building sustainable competitive advantage. MSME leaders are encouraged to enhance employee empowerment, nurture creativity, and embrace digital leadership to drive innovation.